The Reproduction of “Petro-Nationalism” in Ethnic Media: A Case Study of WeChat Public Accounts’ Coverage of the Trans Mountain Pipeline Controversy - Chen, Sibo (Frontiers in Environmental Science, 2021)
Over the past two decades, Alberta’s bitumen industry has emerged as a major point of contention in Canadian politics, with the Trans Mountain pipeline expansion (TMX) project being a recent controversy that has attracted both domestic and international media attention. This brief research report focuses on news coverage of TMX in a rarely studied form of ethnic media: WeChat newsfeeds (known as “public accounts”) targeting Chinese diasporas across Canadian metropolises. A thematic analysis of TMX-related WeChat articles published between January 2016 and May 2021 reveals an overall negative attitude toward the project’s opponents. This stance is mainly due to WeChat public accounts’ heavy reliance on the Canadian mainstream media’s framing of TMX. As a result, the Canadian mainstream media's downplay of the climate emergency and decarbonization sets the news agendas of the surveyed WeChat public accounts. Accordingly, there is an urgent need to develop non-English alternative media to engage ethnic minority groups in broader public conversations on climate change mitigation.